2005
DOI: 10.1103/physrevb.72.014524
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effects on the superconducting properties ofYBa2Cu4O8

Abstract: Measurements of the magnetization under high hydrostatic pressure (up to 10.2 kbar) in YBa2Cu4O8 were carried out. From the scaling analysis of the magnetization data the pressure induced shifts of the transition temperature Tc, the volume V and the anisotropy γ have been obtained. It was shown that the pressure induced relative shift of Tc mirrors essentially that of the anisotropy. This observation uncovers a novel generic property of anisotropic type II superconductors, that inexistent in the isotropic case. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…Bearing these in mind, the discrepancy between the results obtained in the present study and those reported in Ref. [10] can be explained by the difference between the bulk and the surface properties of Li 2 Pd x Pt 3−x B in analogy with what was observed in conventional [19] and unconventional [20] superconductors. We would also like to emphasize that our data are in excellent agreement with the specific heat data presented in Ref.…”
Section: Pdcontrasting
confidence: 92%
“…Bearing these in mind, the discrepancy between the results obtained in the present study and those reported in Ref. [10] can be explained by the difference between the bulk and the surface properties of Li 2 Pd x Pt 3−x B in analogy with what was observed in conventional [19] and unconventional [20] superconductors. We would also like to emphasize that our data are in excellent agreement with the specific heat data presented in Ref.…”
Section: Pdcontrasting
confidence: 92%
“…In order to extract the second moment of P (B) we used a similar procedure as described in Ref. [16]. All µSR time spectra were fitted by a three component expression:…”
mentioning
confidence: 99%
“…Many materials become superconducting under a certain pressure, including Bi 2 Te 3 , Sb 2 Se 3 , H 2 S, and WTe 2 1416 , motivating many researchers to direct their attention to pressure-induced superconductors. However, most of these efforts have focused on the exertion of hydrostatic pressure 14, 15, 1721 and element substitution 3, 2225 . Direct loading on superconductor materials with dynamic high temperature and high pressure has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%